Structural interconversion of alternating purine-pyrimidine inverted repeats cloned in supercoiled plasmids. - Klysik, J (1988)
Two self complementary oligonucleotides, T(GC)4AT(GC)4ACATG and C(GC)2(AT)5 (GC)3ATG, were synthesized and cloned into plasmids. Negative supercoiling causes a structural transition in the primary helix of both inserts. The first sequence converts into the left-handed helix, whereas the second sequence undergoes a transition into a cruciform or a Z-type structure depending on the experimental conditions employed. This has been deduced from the mapping of S1 nuclease sensitive sites, OsO4-sensitive sites, DEP modification pattern and relaxation studies. In addition, the differential effect of 5-cytosine methylation and binding of the AT-specific drug distamycin on these transitions further supports this interpretation. Thus, it is demonstrated, that the same sequence which is both inverted repeat and alternating purine-pyrimidine type may adopt either the left-handed conformation or the cruciform structure in response to the superhelical stress. Formation of the Z-type helix can be transmitted through the d(AT)n region which is 10 bp in length.